Bistable rotating mechanism based on dielectric elastomer actuator. (22nd November 2019) - Liu, Yide; Liu, Binhong; Yin, Tenghao; Xiang, Yuhai; Zhou, Haofei; Qu, Shaoxing
Abstract: A growing number of dielectric elastomer actuators have been proposed to build soft robots and soft electronic devices. However, it remains a big challenge to design soft bistable actuators. Most of existing bistable actuators based on soft materials generate either limited actuation range or unrepeatable actuation. In this article, we present a new bistable rotating mechanism using dielectric elastomer actuators, which exhibits a relatively large actuation angle range and repeatable motion. The mechanism is featured by an antagonistic structure with mechanical locks to create two symmetric stable configurations. We develop an analytical model to help design and explain the electromechanical behavior of the bistable rotating mechanism. Powered by the dielectric elastomer actuators, it shows fast response and large load capability. We build a binary manipulator to further demonstrate that the bistable rotating mechanism can provide a promising route for the design of binary systems.